Circulating levels of cardiac troponin T are associated with coronary noncalcified plaque burden in HIV-infected adults: a pilot study. (March 2019) - Foster, Parker; Sokoll, Lori; Li, Ji; Gerstenblith, Gary; Fishman, Elliot K; Kickler, Thomas; Chen, Shaoguang; Tai, Hong; Lai, Hong; Lai, Shenghan
HIV infection and/or antiretroviral therapy may increase the risk of subclinical coronary atherosclerosis. However, patients with chronic kidney disease (CKD) and those without IV access cannot undergo contrast-enhanced coronary CT angiography (CCTA). This study was to explore the relationship between cardiac troponin T (cTnT) levels and the extent of coronary plaque burden, as assessed by CCTA in those with HIV infection. Between June and September 2017, 58 HIV-infected participants were recruited and underwent contrast-enhanced CCTA. cTnT was measured with the Elecsys Troponin T Gen 5 STAT assay, and noncalcified plaque burden was quantified using coronary plaque analysis. Robust regression model was employed to perform primary statistical analysis. Univariate robust regression analysis indicated that male gender, cardiovascular risk score defined by the 2013 ACC/AHA cardiovascular risk score algorithm, and cTnT levels were significantly associated with noncalcified plaque volume index (NCPI). Final robust regression analyses showed that only cTnT (log scale) was independently associated with the NCPI (regression coefficient: 0.0453 with 95% CI: 0.0151, 0.0755, p = 0.003). These results of this study suggest that cTnT may be a promising marker for coronary plaque burden, especially in patients with HIV-associated CKD or without IV access.